News-reporting and ideology in 17th-century English murder pamphlets: from paratext to text - Cecconi, Elisabetta (Cambridge Scholars Publishing, 2024)
This book follows the evolution of news reporting in 17th-century murder pamphlets and explores how persuasive discourse features were used, modified and re-adapted over the decades in order to bias people's perception of crime and justice in relation to the ideological imperatives of the time. Originally presented as moralizing publications aimed at safeguarding the social well-being of the country, murder pamphlets became an object of political propaganda in the years of the Irish Rebellion and the English Civil War and developed into a gradually more secularized source of public information towards the end of the century. This text analyses the process and motivations behind the choice of authenticating discourse strategies, scripts and reality paradigms used by news writers at the level of the paratext and the text in order to sensitize readers towards issues of divine retribution and criminal justice. In light of the socially inclusive character of the murder pamphlet, particular attention is devoted to the religious and political appropriation of the genre in post-Reformation England, in the turbulent period of the Irish Rebellion and the English Civil War and in the post-Restoration era. Based on a solid theoretical framework and a thorough methodological apparatus, this study provides the reader with many examples to facilitate understanding and offers a model of analysis for investigating aspects of the paratext and the text which can be applied to other forms of news-related cheap print in the Early Modern period